The German S3 guideline prostate cancer - Wenz, Frederik; Martin, Thomas; Böhmer, Dirk; Martens, Stefan; Sedlmayer, Felix; Wirth, Manfred; Miller, Kurt; Heidenreich, Axel; Schrader, Mark; Hinkelbein, Wolfgang; Wiegel, Thomas (Strahlentherapie und Onkologie, 2010)
This report summarizes the relevant aspects of the S3 guideline prostate cancer for the radiation oncologist. Treatment decision and dose prescription are discussed, as well as technical performance of external beam radiotherapy and brachytherapy. The relevant literature is cited to allow an overview of the current recommendations.